A New Approach to Estimating the T-Year Return-Period Wave Height - Zhang, Jun; Song, Wenpeng; Ge, Yong (Journal of Ocean University of China, 2011)
The paper introduces a new approach to estimating the T-year return-period wave height （TRPW）, i.e. the wave height expected to occur in T-year, from two sets of observed extreme data and on the basis of the maximum entropy principle. The main points of the approach are as follows. 1） A maximum entropy probability density function （PDF） for the extreme wave height H is derived from a Euler equation subject to some necessary and rational constraints. 2） The parameters in the function are expressed in terms of the mth moment of H. 3） This PDF is convenient to theoretical and practical applications as it is simple and its four parameters are easy to be determined from observed extreme data. An example is given for estimating the TRPW in 50 and 100 years by the present approach and by some currently used methods using observed data at two hydrographic stations.The comparison of the estimated results shows that the present approach is quite similar to the Pearson-Ⅲ and Gumbel methods.